Crossing the boundaries of imagination: The role of a public library exhibition in global learning for student teachers and teacher educators. (April 2020) - Hickling-Hudson, Anne; Hepple, Erika
Abstract: In this paper, we utilise the theoretical concept of 'boundary crossing' to explore how, as Australian university teacher educators, we worked with library curators and a class of student teachers to mount a public exhibition of their group work. We consider how the students crossed 'boundaries of imagination' in symbolic representation and critical analysis by creating artistic installations to express global education themes. We reflect on what we, the university educators, learned about crossing institutional and pedagogical boundaries to mutually facilitate new learning. We argue for the importance of shared public pedagogy as offering new avenues for teacher education and of connecting with local communities. Highlights: Student teachers designed a library exhibition on global education themes. University and library staff collaborated to engage students in 'public pedagogy'. In their exhibition work, students 'crossed the boundaries of imagination' into symbolic, three-dimensional representation. University and library colleagues crossed institutional boundaries to mutually facilitate new learning. The project introduced participants to a relational way of promoting public global learning.